HIỆU LỰC TÁC DỤNG CỦA CHẾ PHẨM THUỐC TIÊM FENTANYL NGHIÊN CỨU BÀO CHẾ TRONG NƯỚC - Vũ, Mạnh Hùng; Lê, Thị Hồng Hạnh; Phạm, Duy Nam (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON EFFICACY OF DOMESTICALLY STUDIED AND MANUFACTURED FENTANYL CITRATE INJECTION This paper presents the evaluation of efficacy of domestically studied and manufactured fentanyl injections on experimented animals. Fentanyl citrate injections (ampoules of 500 μg, 10ml) of Roxtemedica Company (Germany) are used as the reference drug. Analgesic effect is studied on the mice by hot plate induced pain model and acetic acid induced "writhing test". The product is applied in the surgical practices on dogs (involved 10 types of surgery). The parameters such as heart rate, respiration rate, blood pressure and volume of used fentanyl citrate injection (mL; mL/min; mL/min.kg) are recorded. The study results show that fentanyl citrate have strong analgesic and anesthesic effects. The studied injection is completly effective when used for anesthesia and analgesia in surgical practice. Fentanyl citrate does not cause contractions on bronchus smooth muscle of guinea pig. All the results show that the fentanyl injections have equivalent effects as the reference drug.